Locoregional treatment versus no treatment of the primary tumour in metastatic breast cancer: an open-label randomised controlled trial. Issue 13 (October 2015) - Badwe, Rajendra; Hawaldar, Rohini; Nair, Nita; Kaushik, Rucha; Parmar, Vani; Siddique, Shabina; Budrukkar, Ashwini; Mittra, Indraneel; Gupta, Sudeep
Summary: Background: The role of locoregional treatment in women with metastatic breast cancer at first presentation is unclear. Preclinical evidence suggests that such treatment might help the growth of metastatic disease, whereas many retrospective analyses in clinical cohorts have suggested a favourable effect of locoregional treatment in these patients. We aimed to compare the effect of locoregional treatment with no treatment on outcome in women with metastatic breast cancer at initial presentation. Methods: In this open-label, randomised controlled trial, we recruited previously untreated patients (≤65 years of age with an estimated remaining life expectancy of at least 1 year) presenting with de-novo metastatic breast cancer from Tata Memorial Centre, Mumbai, India. Patients were randomly assigned (1:1) to receive locoregional treatment directed at their primary breast tumour and axillary lymph nodes, or no locoregional treatment, by a computer-generated block randomisation sequence (block size of four). Randomisation was stratified by site of distant metastases, number of metastatic lesions, and hormone receptor status. Patients with resectable primary tumour in the breast that could be treated with endocrine therapy were randomly assigned upfront, whereas those with an unresectable primary tumour were planned for chemotherapy before randomisation. Of the patients who had chemotherapy before randomisation, we randomly assigned patients who had an objective tumour response after six to eight cycles of chemotherapy. The primary endpoint was overall survival analysed by intention to treat. This study is registered withClinicalTrials.gov, NCT00193778 . Findings: Between Feb 7, 2005, and Jan 18, 2013, of the 716 women presenting with de-novo metastatic breast cancer, we randomly assigned 350 patients: 173 to locoregional treatment and 177 to no locoregional treatment. At data cut-off of Nov 1, 2013, median follow-up was 23 months (IQR 12·2–38·7) with 235 deaths (locoregional treatment n=118, no locoregional treatment n=117). Median overall survival was 19·2 months (95% CI 15·98–22·46) in the locoregional treatment group and 20·5 months (16·96–23·98) in the no-locoregional treatment group (HR 1·04, 95% CI 0·81–1·34; p=0·79), and the corresponding 2-year overall survival was 41·9% (95% CI 33·9–49·7) in the locoregional treatment group and 43·0% (35·2–50·8) in the no locoregional treatment group. The only adverse event noted was wound infection related to surgery in one patient in the locoregional treatment group. Interpretation: There is no evidence to suggest that locoregional treatment of the primary tumour affects overall survival in patients with metastatic breast cancer at initial presentation who have responded to front-line chemotherapy, and this procedure should not be part of routine practice. Funding: Department of Atomic Energy, Government of India.